Socialist movie making vs. Gosplan. Establishing an infrastructure for the soviet amateur cinema - Vinogradova, Maria (Iluminace, 2016)
The study, based on careful research of primary archival sources, both written and film, describes the very gradual process of the establishment of amateur cinema in the hierarchy of Soviet cinema. The author also reveals the reasons why the atypical 35mm format was used elsewhere for amateurs in the Soviet Union even after the war.
Keywords: amateur film; film technology; politics and film; political systems and film